Leaf Nutrient Resorption and Export Fluxes of Avicennia marina in the Central Red Sea Area - Almahasheer, Hanan; Duarte, Carlos M.; Irigoien, Xabier (Frontiers in Marine Science, 2018)
Red Sea mangroves occur in an oligotrophic sea without permanent freshwater inputs. Understanding the mechanisms to cope with nutrient limitation is, therefore, important to understand their distribution and nutrient dynamics in coastal ecosystems. We measured total number of meristems to estimate their leaves production and nutrients (N, P, and Fe) as a function of age in Avicennia marina leaves. Then estimated resorption rates; the recovery of nutrients from senescing leaves before they are shed in a total of 91 leaf from four different mangroves stands in the Central Red Sea. We found that the concentration of N and P but not Fe declined with age. Nutrient content also declined in the older leaves with high resorption capacity of 69% and 72% in N and P vs. low resorption of 42% in Fe. The role of Fe resorption is poorly studied in plants, nevertheless, this study could provide an insight into our knowledge of iron resorption in the mangroves, which has never been assessed before. The leaf nutrient export flux from senescing leaves in monospecific stand of Avicennia marina was 9, 0.4 and 1 g m-2 y-1 for N, P and Fe respectively, suggesting mangrove litter-fall to be an important source of bioavailable iron in particular, due to its low resorption, to the adjacent oligotrophic ecosystem.